Effect of γ-lactones and γ-lactams compounds on Streptococcus mutans biofilms - Mariane Beatriz Sordi; Thaís Altoé Moreira; Juan Felipe Dumes Montero; Luis Cláudio Barbosa; César Augusto Magalhães Benfatti; Ricardo de Souza Magini; Andréa de Lima Pimenta; Júlio César Matias de Souza (University of São Paulo, 2018)
Abstract Considering oral diseases, antibiofilm compounds can decrease the accumulation of pathogenic species such as Streptococcus mutans at micro-areas of teeth, dental restorations or implant-supported prostheses. Objective To assess the effect of thirteen different novel lactam-based compounds on the inhibition of S. mutans biofilm formation. Material and methods We synthesized compounds based on γ-lactones analogues from rubrolides by a mucochloric acid process and converted them into their corresponding γ-hydroxy-γ-lactams by a reaction with isobutylamine and propylamine. Compounds concentrations ranging from 0.17 up to 87.5 μg mL-1 were tested against S. mutans. We diluted the exponential cultures in TSB and incubated them (37°C) in the presence of different γ-lactones or γ-lactams dilutions. Afterwards, we measured the planktonic growth by optical density at 630 nm and therefore assessed the biofilm density by the crystal violet staining method. Results Twelve compounds were active against biofilm formation, showing no effect on bacterial viability. Only one compound was inactive against both planktonic and biofilm growth. The highest biofilm inhibition (inhibition rate above 60%) was obtained for two compounds while three other compounds revealed an inhibition rate above 40%. Conclusions Twelve of the thirteen compounds revealed effective inhibition of S. mutans biofilm formation, with eight of them showing a specific antibiofilm effect.